2022
DOI: 10.1093/ehjci/jeac050
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological maladaptive changes in the explanted human mitral leaflets correlate with changes in echocardiographic leaflet morphology and the severity of ischaemic mitral regurgitation

Abstract: Aims Several changes of the mitral valve (MV) morphology have been previously documented in ischaemic mitral regurgitation (IMR) upon macro and microscopic examination. This study aimed to correlate echocardiographic MV thickening with IMR severity and to delineate the histopathological basis of valve thickening from the explanted leaflets. Methods and results Two hundred and fifty patients were included in the echo-group; of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“… 27 Moreover, comparison of human mitral valve regurgitation detected by echocardiography with histopathology of explanted tissue after repair supports a correlation between valve leaflet thickening and the extent of dysfunction. 28 In MFS, MVD often precedes the development of aortic aneurysm, and the dilated aortae in MFS mice and human patients do not exhibit increased immune cells. 9 Thus, alternative therapies may be needed to treat aortic dilation characteristic of MFS.…”
Section: Discussionmentioning
confidence: 99%
“… 27 Moreover, comparison of human mitral valve regurgitation detected by echocardiography with histopathology of explanted tissue after repair supports a correlation between valve leaflet thickening and the extent of dysfunction. 28 In MFS, MVD often precedes the development of aortic aneurysm, and the dilated aortae in MFS mice and human patients do not exhibit increased immune cells. 9 Thus, alternative therapies may be needed to treat aortic dilation characteristic of MFS.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, in ischemic MR a short AL is very frequent. Avila‐Vanzzini et al, 10 when ischemic MR was moderate or more, found an AL length of 24mm or less in 50% and 22 mm or less in 25% of the cases.…”
Section: Surgical Strategiesmentioning
confidence: 98%